The doctrine of the two depressions in historical perspective - Shorter, E. (2007)
OBJECTIVE: To determine if the concept of two separate depressions –melancholia and non-melancholia – has existed in writings of the main previous thinkers about mood disorders. METHOD: Representative contributions to writing on mood disorders over the past hundred years have been systematically evaluated. RESULTS: The concept of two separate depressions does indeed emerge in the psychiatric literature from the very beginning of modern writing about the concept of ‘melancholia’. For the principal nosologists of psychiatry, melancholic depression has always meant something quite different from non-melancholic depression. Exceptions to this include Aubrey Lewis and Karl Leonhard. Yet the balance of opinion among the chief theorists overwhelmingly favors the existence of two quite different illnesses. CONCLUSION: The concept of ‘major depression’ popularized in DSM-III in 1980 is a historical anomaly. It mixes together psychopathologic entities that previous generations of experienced clinicians and thoughtful nosologists had been at pains to keep separate. Recently, there has been a tendency to return to the concept of two depressions: melancholic and non-melancholic illness. ‘Major depression’ is coming into increasing disfavor. In the next edition of DSM (DSM-V), major depression should be abolished; melancholic mood disorder (MMD) and non-melancholic mood disorder (NMMD) should become two of the principle entities in the mood disorder section.